Optimizing the Effectiveness of Hospital Health Promotion Implementation at Simpang Lima Gumul Regional Hospital, Kediri Regency - Rahmania Ambarika; Moh Khoirul Anam; Erick Berto Yahya; Seno Arif Amrullah; Alfi Yudisianto (Journal of Community Engagement in Health, 2025)
Hospital Health Promotion is an important function in health care settings that aims to empower patients, families and communities to actively participate in health maintenance and improve well-being. This study analyzed the implementation of Hospital Health Promotion in Simpang Lima Gumul Kediri Hospital to identify factors that influence its effectiveness and develop optimization strategies. A mixed approach was used in this study, including interviews with hospital management and staff, analysis of hospital documents, and review of relevant literature. The results showed that although the hospital has implemented various Hospital Health Promotion programs, there are several challenges that hinder its full potential, lack of training for hospital health promoters, lack of communication among staff, suboptimal program evaluation, and attitudinal barriers from some implementers that hinder the effectiveness of Hospital Health Promotion. To overcome these challenges, the management of Simpang Lima Gumul Hospital in Kediri needs to optimize its Health Promotion program through regular monitoring and evaluation. This process will be supported by a self-assessment form to simplify the evaluation and will include efforts to identify problems, strengthen human resources, develop innovative and integrated programs, utilize technology, increase collaboration with external partners, and measure program achievements for continuous improvement. Implementing this strategy is expected to increase the effectiveness of the hospital's health promotion program and contribute to better health outcomes for the community it serves.